2022
DOI: 10.3390/s22103790
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Bandwidth of Pressure Sensors Dedicated to Blast Experiments

Abstract: New broadband (>1 MHz) pressure sensors are regularly reported in the literature to measure the overpressure of blast waves. However, the frequency bandwidth needed to accurately measure such overpressure has not yet been clearly discussed. In this article, we present a methodology to determine the bandwidth required to estimate the overpressure magnitude at the front of a blast wave, in order to obtain a desired estimation accuracy. The bandwidth is derived here by using Kingery and Bulmash data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…We show that the characterization, in the frequency domain, of a pressure measurement chain is of prime importance since it can facilitate the true impact evaluation of optimized devices relative to commercial ones. A better understanding of the useful bandwidth is an important parameter since Chalnot et al have shown its importance in estimating the overpressure magnitude at the blast wave front, to obtain the desired accuracy [ 32 ].…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…We show that the characterization, in the frequency domain, of a pressure measurement chain is of prime importance since it can facilitate the true impact evaluation of optimized devices relative to commercial ones. A better understanding of the useful bandwidth is an important parameter since Chalnot et al have shown its importance in estimating the overpressure magnitude at the blast wave front, to obtain the desired accuracy [ 32 ].…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…In the far field, where the explosion is sufficiently distant that only the propagating air shock interacts with the structure, reliable semi-empirical predictive methods exist for both the positive [ 2 ] and negative [ 3 ] phases of the blast wave for spherical and hemispherical charges. Well-controlled experimental studies using commercially available piezo-resistive or piezo-electric pressure sensors have repeatedly shown these methods to be accurate for scaled distances m/kg [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%